Arkeologi og myter:: Om Nidarosdomens historie før 1200 - Ekroll, Øystein (Hikuin, 2006)
Myths and Archeology: The History of Nidaros Cathedral before 1200 AD By Øystein Ekroll The early history of Nidaros Cathedral and its surrounding area has hitherto been a carefully constructed house of cards, based on pious legends dating back to at least the 13th century, with the aim to give the site a continous Christian tradition dating back to 1030. The Cathedral of Nidaros and the medieval Archbishop’s Palace are situated on the southern part of the Nidarnes peninsula. The medieval town of Nidaros/ Trondheim was situated on the northeastern part of the peninsula, along the west bank of the river Nid. The cathedral complex occupies the highest part of the peninsula, a plateau situated c.14 meters above sea level. In the middle ages the royal residence lay by the river, to the east of the cathedral, and the canonical residences were situated north of the cathedral. According to traditions from the early 13th century, the main altar of the cathedral is placed on the spot where the body of King Olav Haraldson (St Olav) was secretly buried in a desolate area outside Trondheim for one year after his death in the battle of Stiklestad on July 29, 1030. The 12 meters deep well next to the altar has been identified with the source with healing water which, according to the same legend, sprang up next to the grave. The site of the mid-11th century church of St. Mary, demolished in the 1160s by Archbishop Øystein Erlendsson, has since the 1880s been located to a point 30 meters northeast of the cathedral. This assumption is based on some fragmentary remains of masonry excavated in 1887, and a passage in an Icelandic saga manuscript from the late 15th century, which claims that the tribune for the popular acclamation of Norwegian kings which stood here, was built above the site of the altar of St. Mary’s Church. This story has been carefully retold by generations of historians until today. But a critical reinterpretation of the original sources, combined with new archeological excavations in the area, has given another story. This plateau, far from being desolate in 1030, was filled with agricultural activity, and was probably the site of the manor of Nidarnes, mentioned around 1000 AD, when it was confiscated by the king. The archeological evidence for St. Mary’s Church turns out to be false, as the presumed »chancel« of the church must be a vaulted basement, probably from a tower connected to the royal residence. The first cathedral, the predecessor of the present one, was probably built within the royal precinct as a royal palace church, and presumably was given to the bishop in the early 12th century, when a new St. Nicholas Church was built as a Royal chapel. The later function of St. Mary’s Church and why it was demolished remains a mystery. The original burial place of St. Olav was probably on a sand bank next to the river Nid, where a source with excellent water still exists. This has locally been associated with St. Olav for at least 200 years, but ignored by most historians. However, no cathedral could be built here, so the burial site had to be transferred to a new site: The highest point of the peninsula, where the main altar of the Cathedral still stands. In order for the site to be convincing for pilgrims, a well was dug a few meters from the altar and presented as the true source. This »pious fraud« was convincing enough to be accepted until today.